Korupsi dan Money Laundering (Studi Kasus Indonesia Dan Korea Selatan Merusak Sistem Sosial Dan Keuangan Global) - Syahrudin (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Abstract Corruption in Indonesia and in other countries has become a latent problem and is very difficult to eradicate. Various attempts have been made to eradicate this corruption: both at the country level itself and at the international level. In general, the eradication of corruption is carried out through the establishment of a corruption eradication agency or institution which is legalized through a law. Furthermore, the following presentation is a case study of Indonesia and South Korea on how to eradicate corruption. The practice of money laundering has often involved cross-border transactions, because by conducting such transactions between countries, it is very effective in eliminating traces of illegal flows of funds. With the increasing globalization of the international financial system, money laundering, as a criminal activity, is becoming more and more common, but in turn it greatly affects and damages the global social and financial system. In summary, it can be concluded that in the era of globalization the problem of corruption and money laundering is becoming increasingly widespread because the existence of this crime involves many factors that cross national boundaries. The problem of corruption and money laundering is the dark side of globalization. Handling corruption and money laundering cannot be resolved quickly and easily, but it takes time, commitment, political will, and support from all parties: national government, society, and multilateral cooperation. Learning from South Korea, Indonesia and the international community, for example, requires a more efficient structure-based bureaucratic reform by upholding the spirit of 'Good Governance' and 'Check and Balance' which is expected to encourage all elements of the nation to work together to solve corruption at a practical level. Keywords: CORRUPTION, MONEY LAUNDERING, GLOBALIZATION Abstrak Korupsi di Indonesia dan di negara-negara lain merupakan hal yang sudah menjadi masalah laten dan sangat sulit untuk diberantas. Berbagai usaha dilakukan untuk mcm-berantas korupsi in: baik di tingkat negara itu sendiri maupun di tingkat internasional. Pada umumnya, pemberantasan korupsi ini dilakukan mclalui pembentukan suatu badan atau Icmbaga pemberantasan korupsi yang disahkan meialui suatu undang-undang. Se-lanjutnya, paparan berikut adalah studi kasus Indonesia dan Korea Selatan tentang bagai-mana pemberantasan korupsi dilakukan. Praktik money laundering sejak dulu seringkali me-libatkan transaksi lintas batas, karena dengan melakukan transaksi antarnegara seperti itu, sangat efektif untuk menghilangkan jejak aliran dana ilegal. Dengan semakin berkem-bangnya globalisasi sistem keuangan internasional, money laundering, sebagai aktivitas kejahatan menjadi marak, namun pada gilirannya sangat memengaruhi dan merusak sistem sosial dan keuangan global. Secara ringkas bisa disimpulkan bahwa di era globalisasi masalah korupsi dan pen-cucian uang menjadi semakin marak karena eksistensi dari tindak kejahatan ini melibatkan banyak faktor penyebab yang melintasi batas-baias nasional. Masalah korupsi dan money laundering merupakan sisi gelap dari globalisasi. Penanganan korupsi dan pencucian uang tidak dapat diselesaikan dengan cepat dan mudah, tetapi perlu waktu, komitmen, political will, dan dukungan semua' pihak: pemerintah nasional, masyarakat, dan kerja sama multilateral. Belajar dari Korea Selatan, Indonesia dan komunitas internasional, misalnya membutuhkan reformasi birokrasi berbasis struktur yang lebih efisien dengan menjunjung semangat 'Good Governance' dan 'Check and Balance' yang diharapkan dapat mendorong semua elemen bangsa untuk bersama-sama menyelesaikan penanganan korupsi hingga tataran praktis Kata Kunci: KORUPSI, MONEY LAUNDERING, GLOBALISASI